Long-term follow-up of children treated with the Repiphysis expandable prosthesis for lower extremity bone sarcoma. Issue 2 (7th June 2021) - Masrouha, Karim; Abboud, Miguel; Saab, Raya; Muwakkit, Samar A.; Khoury, Nabil; Haidar, Rachid; Saghieh, Said
Abstract : Expandable endoprostheses provide a limb salvage option for skeletally immature patients with bone sarcoma of the lower extremities. Initial reports of the Repiphysis prosthesis were encouraging; however, medium-term follow-up revealed high complication rates. We report on the long-term follow-up of a cohort of patients treated with the Repiphysis prosthesis. Eleven patients were included in the study. Data collected included sex, age at surgery, duration of follow-up, site of disease, histologic diagnosis, number of lengthening sessions, amount lengthened, postoperative complications, endoprosthetic failure, mode of endoprosthetic failure, duration from index surgery to failure and to revision, type of revision surgery and final limb-length discrepancy. The average duration of follow-up from the time of surgery was 180 months (range, 144–215 months). Fifteen Repiphysis implants were used in 11 patients. All implants failed with an average time from surgery to failure of 36 months (range, 3–72 months). Twenty-four complications were observed: one wound dehiscence, two deep infections, 18 mechanical failures, implant collapse with destruction of proximal tibia epiphysis in two and one periprosthetic proximal femur fracture with dislodgement of the stem. Despite being an option for limb salvage, the Repiphysis prosthesis has a high rate of mechanical failure and need for revision, similar to other expandable implants. The authors, therefore, recommend full disclosure of the potential short- and long-term complications and need for revision, as well as alternative treatment options if their use is considered. Level of evidence: IV (Therapeutic).